ANALISIS KONSUMSI BAHAN BAKAR DAN EFISIENSI BOILER MENGGUNAKAN FUEL OIL ADDITIVE - Moch. Syaiful Anwar; Mochamad Shaleh (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2023)
The increasing demand for electrical energy requires thermal power plants to improve operational efficiency while reducing fuel consumption and energy losses. This study investigates the effect of fuel oil additive on boiler efficiency and fuel utilization in a steam power plant system. The research applied an experimental quantitative approach using a comparative before–after method by evaluating boiler performance prior to and following the application of the additive. Operational data were collected directly from the plant monitoring system, including boiler load, fuel consumption, steam generation, flue gas conditions, and boiler efficiency parameters. Boiler efficiency calculations were conducted using the ASME PTC 4.1 input–output performance test method. The results indicate that the application of fuel oil additive improved boiler efficiency from 93.357% to 98.922%, representing an increase of 5.565%. In addition, the plant load increased from 79.50 MW to 81.00 MW after additive utilization. The improvement in performance is associated with better fuel atomization, enhanced combustion quality, and reduced heat losses during boiler operation. The findings demonstrate that the use of fuel oil additive can contribute to more efficient boiler operation, lower fuel consumption, and improved thermal performance in steam power plants.